2016
DOI: 10.1016/j.ejvs.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Imaging Markers as Predictors of Abdominal Aortic Aneurysm Growth or Rupture: A Systematic Review

Abstract: Although PWS is significantly higher in symptomatic or ruptured AAAs in most FEA studies, confounding bias, clinical heterogeneity, and lack of standardisation limit the interpretation and generalisability of the results. Also, there is conflicting evidence on whether increased wall stress is associated with growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…To predict and prevent early aneurysm rupture and to improve the selection for AAA repair, additional risk factors besides diameter and growth rate must be considered, for example biomechanical properties, 24 intra-luminal thrombus biomarkers, 25e27 or volume. 10,11 In a prospective 3D-CT study of 57 patients with 14 months of follow-up, Parr et al demonstrated that almost half of the patients with volume growth did not display a concomitant diameter increase, supporting the present findings acquired non-invasively with 3D-US.…”
Section: Discussionmentioning
confidence: 99%
“…To predict and prevent early aneurysm rupture and to improve the selection for AAA repair, additional risk factors besides diameter and growth rate must be considered, for example biomechanical properties, 24 intra-luminal thrombus biomarkers, 25e27 or volume. 10,11 In a prospective 3D-CT study of 57 patients with 14 months of follow-up, Parr et al demonstrated that almost half of the patients with volume growth did not display a concomitant diameter increase, supporting the present findings acquired non-invasively with 3D-US.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, PWS had increased sensitivity (94% vs. 81%), accuracy (85% vs. 73%) and specificity (81% vs. 70%) as a predictor of rupture-risk relative to maximum diameter [ 27 ]. A further systematic review highlighted a number of methodological weaknesses of prior studies [ 28 ]. There is therefore remaining uncertainty about the value of measuring PWS to predict AAA rupture [ 28 ].…”
Section: Biomechanics Forces and Aaa Rupturementioning
confidence: 99%
“…A further systematic review highlighted a number of methodological weaknesses of prior studies [ 28 ]. There is therefore remaining uncertainty about the value of measuring PWS to predict AAA rupture [ 28 ].…”
Section: Biomechanics Forces and Aaa Rupturementioning
confidence: 99%
“…This paradox of stated and used diameters is rarely reflected upon in standard care [13,14]. Even if aneurysm diameter growth is reported to be more accurately predicted by aneurysm volume than diameter [15], and biomechanical analysis of AAAs has been shown to outperform diameter measurements in both growth and rupture risk prediction [16,17], diameter is still the gold standard for surveillance and threshold for elective repair [13].…”
Section: Introductionmentioning
confidence: 99%